2016
DOI: 10.7874/jao.2016.20.3.168
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Aspects and Surgical Outcomes of Congenital Cholesteatoma in 93 Children: Increasing Trends of Congenital Cholesteatoma from 1997 through 2012

Abstract: Background and ObjectivesThe recent increase in the reported incidence of congenital cholesteatoma (CC) may be secondary to the widespread use of otoendoscopy as well as an increased awareness of these lesions among primary care physicians. However, little research about CC has been conducted in a large group of patients. This study aimed to analyze the clinical characteristics of CC including the annual number of patients, symptoms, age at diagnosis, stage and type of disease, surgical techniques, recurrence,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 12 publications
2
19
0
Order By: Relevance
“…Additionally, several features of the CCs in this study were consistent with the findings from previous reports on this disorder [6][7][8][9][10][11]. For instance, unilateral conductive hearing loss was the most frequent presentation.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Additionally, several features of the CCs in this study were consistent with the findings from previous reports on this disorder [6][7][8][9][10][11]. For instance, unilateral conductive hearing loss was the most frequent presentation.…”
Section: Discussionsupporting
confidence: 92%
“…The incidence of CC is reportedly less than 1 per 100,000 children [4,5]. It mostly occurs in boys, with average ages of 4-14 years at diagnosis [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…17 The study done by Cho et al also shown similar mean age of 6.1 years. 13 Though this condition is congenital, often the diagnosis is delayed because CC may grow for years without causing signs or symptoms and, having grown without early detection. 18 In the present study, all the cases have unilateral ear involvement with right ear more involved.…”
Section: Methodsmentioning
confidence: 99%
“…In a study done by Cho et al, all 93 patients had unilateral ear involvement. 13 Particular attention must be paid to the status of the ears of children to complain about symptoms associated with cholesteatoma, especially when presentations are subtle or unilateral. 19 Out of 46 patients, 14 (30.43%) patients were asymptomatic and CC were found incidental in the present study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation